Cell‐free nucleic acids are present in blood products and regulate genes of innate immune response. Issue 7 (17th April 2018) - Waldvogel Abramowski, Sophie; Tirefort, Diderik; Lau, Pierre; Guichebaron, Arthur; Taleb, Sofiane; Modoux, Christine; Lemoine Chaduc, Coralie; Bruyere Cerdan, Pascale; Roux Lombard, Pascale; Lecompte, Thomas; Preynat‐Seauve, Olivier
Abstract : BACKGROUND: Extracellular nucleic acids circulate in plasma. They are expected to be present in manufactured blood products eligible for transfusion, but little is known about their biological activity on human cells. The aim of this study is to investigate whether cell‐free nucleic acids (CFNAs) are present and biologically active in red blood cell units (RBCUs), fresh frozen plasmas, and platelet concentrates. STUDY DESIGN AND METHODS: CFNAs were extracted from RBCUs, fresh frozen plasma, and platelet concentrates. Their nature and structure were analyzed by regular methods of nucleic acid detection/quantification. A normalized polymerase chain reaction combining amplification of a CFNA marker (Alu 115) and amplification of an internal nonhuman DNA control spiked in all samples (phiX 174) was developed to study CFNA release after RBCU storage. The impact of CFNAs on gene regulation was tested by microarray after coculture with peripheral blood mononuclear cells and macrophages. RESULTS: Extracellular double‐stranded DNA was present in all blood products, with higher amounts found in cellular suspensions (RBCUs and platelet concentrates). Storage up to 40 days did not influence release from RBCUs, and CFNA amount varied considerably from one unit to another. Microarray experiments showed that exposition of macrophages to CFNA increased the expression of genes involved in the innate immune response including chemokines, chemokine receptors, and receptors of the innate response. CONCLUSION: CFNAs are present in blood products. Immunoregulatory properties of CFNA are shown in vitro, providing new insights on biologically active components of blood products besides those for intended therapeutic use.